PENGEMBANGAN USAHA AGRIBISNIS TERNAK DOMBA DI PETERNAKAN DOMBA BERKAH FARM, JUNREJO, KOTA BATU, JAWA TIMUR - Santoso, Erik Priyo; Rinanti, Rosyida Fajri; Fajariah, Nuraidya; Utomo, Budi; Wawu, Marinus Umbu Kalendi (Universitas Tribhuwana Tunggadewi, 2023)
The purpose of this research is to determine the right marketing strategy to improve the Berkah Farm business. This research was carried out using a survey method which aims to find out which strategy is considered appropriate for developing a sheep farming business. This research was conducted at Berkah Farm, Junrejo, Batu City, East Java. Data was obtained through interviews with the management and employees of Berkah Farm. The data obtained were analyzed using SWOT analysis. Based on the research results, four alternative strategies were offered to develop the business, namely 1) maintaining production quality, 2) conducting disease prevention management training and 3) information technology, 4) maintaining relationships with buyers and marketing agencies